2021
DOI: 10.1016/j.jaad.2020.12.065
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of COVID-19's effect on the timely management of melanoma and nonmelanoma skin cancers

Abstract: 5. Guilpain P, Le Bihan C, Foulongne V, et al. Response to: 'Severe COVID-19 associated pneumonia in 3 patients with systemic sclerosis treated with rituximab' by Avouac et al. Ann Rheum Dis. 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 5 publications
6
46
2
2
Order By: Relevance
“…No difference in the distribution of cases according to Breslow thickness categories was documented in the logistic regression analysis. Our data document that a significant reduction in MM new diagnoses has occurred following the COVID-19 pandemic, similarly to what has been reported for other cancers, [7][8][9] potentially causing an increase of morbidity, mortality and healthcare costs, which could not be quantified at this stage. 10 The number of missed expected cases, based on an estimated 3.4% annual change of melanoma incidence from Veneto regional data, is shown as well.…”
Section: Impact Of the Covid-19 Pandemic On Melanoma Diagnosissupporting
confidence: 77%
“…No difference in the distribution of cases according to Breslow thickness categories was documented in the logistic regression analysis. Our data document that a significant reduction in MM new diagnoses has occurred following the COVID-19 pandemic, similarly to what has been reported for other cancers, [7][8][9] potentially causing an increase of morbidity, mortality and healthcare costs, which could not be quantified at this stage. 10 The number of missed expected cases, based on an estimated 3.4% annual change of melanoma incidence from Veneto regional data, is shown as well.…”
Section: Impact Of the Covid-19 Pandemic On Melanoma Diagnosissupporting
confidence: 77%
“…New melanoma patient in-person visits were reduced significantly, which was not offset by the increase in telemedicine appointments. Asymptomatic follow-up visits were largely deferred, whereas appointments for those with concerning Overall, these delays are in-line with prior publication of estimated diagnostic delays associated with the COVID-19 pandemic [5]. Based on a previously published mean melanoma growth rate (0.11mm/month), our observed delays in screening follow-up patients for new melanoma diagnoses could potentially cause an estimated mean 0.28 mm increase in tumor thickness [6].…”
supporting
confidence: 84%
“…This observation is consistent with other reports describing a clear drop of patient encounters in all levels of the health care system [ 3 ]. Marson et al reported that the number of newly diagnosed cutaneous melanomas dropped by 43.1% during the COVID-19 peak in 2020 (compared to 2019) [ 9 ]. The changes observed during the lockdown period by these authors are comparable to our results, with a 44% and 58% drop in melanoma diagnoses compared to 2018 and 2019, respectively.…”
Section: Discussionmentioning
confidence: 99%